1998
DOI: 10.1139/b98-055
|View full text |Cite
|
Sign up to set email alerts
|

Modalités d'allongement et morphologie des pousses annuelles chez le noyer commun, Juglans regia L. 'Lara' (Juglandaceae)

Abstract: Chez Juglans regia L. 'Lara', des observations bihebdomadaires de l'allongement de trois types morphologiques de pousses annuelles florifères (monocycliques, avec ou sans petit axe à développement immédiat, et bicycliques) en fonction de quatre types de rameaux porteurs ont été réalisées sur des arbres âgés de 4 ans, au cours d'une saison de croissance, dans le Sud-Ouest de la France. Chez les arbres étudiés, l'influence du type de rameau porteur apparaît essentiellement sur les dates de début d'allongement de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
(21 reference statements)
3
9
0
Order By: Relevance
“…Similar to our results, a great variability was proved by many authors when taking into consideration basic architectural traits like tree vigour and growth habit in different local populations as well as in hybrids Botu et al 2001;Kuden et al 1997;Germain 1997b;Germain et al 1997;Lansari et al 2001;Solar et al 2001Zeneli et al 2005), while the quantitative description of annual shoots in walnut was reported only by Ducousso et al (1995), Lauri et al (2001) and Sabatier et al (1998). The first authors dealed with the length and nodes distribution in annual shoots whereas the last ones investigated the current year shoots and their impact to the fruit weight variability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our results, a great variability was proved by many authors when taking into consideration basic architectural traits like tree vigour and growth habit in different local populations as well as in hybrids Botu et al 2001;Kuden et al 1997;Germain 1997b;Germain et al 1997;Lansari et al 2001;Solar et al 2001Zeneli et al 2005), while the quantitative description of annual shoots in walnut was reported only by Ducousso et al (1995), Lauri et al (2001) and Sabatier et al (1998). The first authors dealed with the length and nodes distribution in annual shoots whereas the last ones investigated the current year shoots and their impact to the fruit weight variability.…”
Section: Discussionsupporting
confidence: 90%
“…In Persian walnut (Juglans regia L.), annual shoots were explored from different aspects by many authors like Mauget (1976), Barthélémy et al (1995), Ducousso et al (1995), Sabatier et al (1995Sabatier et al ( , 1998, Sabatier and Barthelemy (2001a) (see Solar andŠtampar 2002). It is common for all of them that they investigated annual shoots from the qualitative point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively homogeneous bud-break period registered here complies with previous observations made for other tree species (Kramer and Kozlowski 1960;Mitchell 1965;Sabatier et al 1995Sabatier et al , 1998Puntieri et al 1998). Bud-break time seems to be under strong genetic control (Kriebel 1957;Morris et al 1957;Irgens-Moller 1960;Walters and Soos 1963), so that homogeneity in this respect would be expected for a population of a vegetatively regenerating species such as N. antarctica.…”
Section: Growth Periodsupporting
confidence: 91%
“…In some cases, however, because lateral resting buds may be 'hidden', during the resting phase, in the axils of persistent basal foliar organs of the terminal bud (Guédès, 1975(Guédès, , 1980 or because lateral axes in an embryonic stage may already exist inside a resting bud (Champagnat, 1965;Roloff, 1985), the interpretation may be complicated or may lead to a misuse of the terminology (Caraglio and Barthélémy, 1997). Finally, in delayed branching it has been shown that the duration of the delay may be of several weeks to a year (Sabatier et al, , 1998(Sabatier et al, , 2003bPuntieri et al, 1998;Heuret et al, 2003) and even several years (Fink, 1983;Nicolini et al, 2001).…”
Section: Branching Processmentioning
confidence: 99%